Translators' Formative Agency in the Periodical Hawar (1932-1943) : The Making of a Kurdish Cultural Identity - Çelik, Dibar, (Brill Kurdish Studies ;, 2025)
The present work uncovers the pivotal role translations in the periodical Hawar played in the formation of a Kurdish cultural identity. In this light, it foregrounds translators' agency and their contributions in novel contexts and thus fills a crucial gap in this area.This work provides new insights into identity formation, focusing on translations in a key magazine published in a minoritized language in the 1930s and 1940s. In this context, it particularly underscores the agency of Celadet Alî Bedirxan as the leading translator and writer as well as the founder and chief editor of the magazine. His vision of Kurdish cultural identity in Hawar had a multilayered characteristic: It was oriented toward a dialogic relationship between Kurdish and western cultures. It proposed the Roman script for Kurdish language dialects and introduced a simple prose style. It also embraced a plural Kurdish religious aspect and led the way to the development of modern Kurdish literature.